2021
DOI: 10.1017/s1047951121004017
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid stenting of the arterial duct with carotid cutdown and flip technique: immediate and early results

Abstract: Stenting of the arterial duct (PDA) has become a standard palliation for ductal-dependent pulmonary circulation. Carotid arterial access provides a direct route for stenting vertical ducts. We evaluated our early results of hybrid ductal stenting via surgical carotid cutdown. Methods and results: In this retrospective single centre cohort study, hybrid PDA stenting was attempted in 11 patients with “flip technique”, between January 2020 and February 2021, and was successful in 10. Median age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…25 diseases, 34 these PDAs can occasionally be accessed through the femoral vein via the right ventricle, ventricular septal defect, and ascending aorta. 35 However, as this pathway may be associated with hemodynamic instability in infants (and requires suitable anatomy), 35 nonfemoral approaches have recently gained favor as potentially more efficient approaches for vertical PDAs.…”
Section: Vascular Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…25 diseases, 34 these PDAs can occasionally be accessed through the femoral vein via the right ventricle, ventricular septal defect, and ascending aorta. 35 However, as this pathway may be associated with hemodynamic instability in infants (and requires suitable anatomy), 35 nonfemoral approaches have recently gained favor as potentially more efficient approaches for vertical PDAs.…”
Section: Vascular Approachmentioning
confidence: 99%
“…Although there is a paucity of large-scale data on vascular access for PDA stenting, multiple smaller observational studies present promising outcomes for the carotid and axillary arteries, particularly for approaching vertical PDAs through the superior aspect of the aortic arch. 25,30,[35][36][37][38][39][40][41] Bauser-Heaton et al 36 observed that carotid and axillary artery access is more commonly used in highly tortuous PDAs than the femoral artery and that procedural and late complications were similar regardless of the access site. Similarly, Alsawah et al 37 reported that percutaneous carotid access was more commonly used in complex ductal anatomy, and they found that both immediate access-related complications and delayed local complications in these cases were significantly lower than in cases that used the femoral artery.…”
Section: Vascular Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 16 , 19 ] These alternative routes allow the practitioner to directly visualize the DA and to complete the procedure with fewer complications. [ 20 ] In our practice, we decide the route after the echocardiographic examination of ductus anatomy. In cases where we decide to use the carotid artery route, we perform the sheath placement process under ultrasound guidance in the safest way.…”
Section: Discussionmentioning
confidence: 99%